Effect of Fasting on Intraocular Pressure: Doi: 10.36351/pjo.v37i1.1083 - Kamal, Zahid; Jamil, Ahmad Zeeshan; Khalid, Muhammad; Ali Bahoo, Muhammad Luqman; Junaid Iqbal, Muhammad; Aziz, Nauman (Pakistan Journal of Ophthalmology, 2020)
Purpose: To determine the effect of fasting on intraocular pressure in fasting individuals. Study Design: Cross sectional observational study. Place and Duration of Study: District Headquarter Teaching Hospital/Sahiwal Medical College Sahiwal, from April 2020 to May 2020. Methods: Four hundred eyes of two hundred healthy fasting subjects were included in this study. Intraocular pressure was measured one week before and during the second week of Ramadan. t-test was used to calculate the difference of means of intraocular pressure one week before and during the second week of Ramadan. Results: Mean age of the subjects was 34.56 ± 12.52 years. IOP in male subjects before and during Ramadan was 14.23 mmHg and 13.20 mmHg respectively, while IOP in female subjects before and during Ramadan was 14.43 mmHg and 13.20 mmHg respectively. Before Ramadan mean intraocular pressure in the right eye was 14.38 ± 3.00 mmHg and in the left eye was 14.21 ± 2.79 mmHg. During Ramadan mean intraocular pressure in the right eye was 13.24 ± 2.87 mmHg and in the left eye was 13.15 ± 2.71 mmHg. t-test indicated that the difference in means of intraocular pressure for right eye one week before and during the second week of Ramadan was 25.74 (p = 0.000). Similarly, the difference in means of intraocular pressure for left eye one week before and during the second week of Ramadan was 41.54 (p = 0.000). Conclusion: Fasting results in a decrease in intraocular pressure in normal population. There was no difference in intraocular pressure changes between male and female subjects. Intraocular Pressure was higher in older age group in both genders. Key Words: Intraocular Pressure, Tonometry, Glaucoma.